Outward Appearance or Inward Significance? On Experts' Perspectives When Studying and Solving Water Scarcity - Pramana, Kharis Erasta Reza; Ertsen, Maurits Willem (Frontiers in Water, 2022)
In the first decade of the 21st century, a water harvesting approach based on contour trenches – ditches to catch runoff – from Kenya was proposed as groundwater recharge technology in a semi-arid area in Ninh Phuoc district, Vietnam. In order to modify this solutions to tackle water scarcity, hydrological conditions at the site needed to be known. For such small-scale interventions, finding the most suitable set of (cheap and quick) efforts to study local hydrology is not easy. After our own study, we explored how different experts evaluated the chosen approach. The results from this evaluation suggest that different perspective for appropriate hydrological research can be found within a group of experts. This finding – in line with anthropologically inspired science studies – suggests that integrating different perspectives from stakeholders when working on suitable solutions in real-life water scarcity situations needs to be complemented with attention for different perspectives on the underlying hydrological processes and how they are to be studied. We discuss how this notion on the multiple perspectives intrinsic to hydrological research can be fruitfully included when developing water interventions.